2011
DOI: 10.1007/s00394-010-0166-z
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of probiotics: are mixtures more effective than single strains?

Abstract: Probiotic mixtures appear to be effective against a wide range of end points. Based on a limited number of studies, multi-strain probiotics appear to show greater efficacy than single strains, including strains that are components of the mixtures themselves. However, whether this is due to synergistic interactions between strains or a consequence of the higher probiotic dose used in some studies is at present unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
245
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(253 citation statements)
references
References 58 publications
3
245
3
2
Order By: Relevance
“…The majority of probiotics currently used are members of lactic acid bacteria (LAB) and, more specifically, strains from the genera Lactobacillus and Bifidobacterium are most commonly used in commercial probiotics. Mixtures of these strains are becoming increasingly popular as researchers gain a deeper understanding of increasing efficacy via possible additive or synergistic effects [124]. Rijkers et al categorised the benefit of probiotics into three levels based on location and method; (1) interference with the growth or survival of pathogenic microorganisms in the gut lumen, (2) improvement of mucosal barrier function or mucosal immune system and (3) influence beyond the gut through the systemic immune system and other organs [125].…”
Section: Modulation By Probioticsmentioning
confidence: 99%
“…The majority of probiotics currently used are members of lactic acid bacteria (LAB) and, more specifically, strains from the genera Lactobacillus and Bifidobacterium are most commonly used in commercial probiotics. Mixtures of these strains are becoming increasingly popular as researchers gain a deeper understanding of increasing efficacy via possible additive or synergistic effects [124]. Rijkers et al categorised the benefit of probiotics into three levels based on location and method; (1) interference with the growth or survival of pathogenic microorganisms in the gut lumen, (2) improvement of mucosal barrier function or mucosal immune system and (3) influence beyond the gut through the systemic immune system and other organs [125].…”
Section: Modulation By Probioticsmentioning
confidence: 99%
“…Pyruvate oxidation was used to assess the activity of pyruvate dehydrogenase (PDH), the enzyme that catalyzes the oxidation of pyruvate and the provision of glucose-derived acetyl CoA to the TCA. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]-pyruvate oxidation was assessed in a similar manner to fatty acid oxidation with the exception that pyruvate was substituted for BSA-bound palmitic acid. All samples were run in triplicate and data were normalized to total protein content and expressed in nmol/mg protein/h.…”
Section: Serum Endotoxin Was Measured With a Pyrogenementioning
confidence: 99%
“…Whether these effects are sustained during longer periods of consuming a high-fat diet is unknown. Importantly, probiotics may have strain-specific antiinflammatory effects (10), and probiotic mixtures may be more effective than single strains in modulating gut bacterial communities and improving immune function (11). In this regard, VSL#3, a commercial multispecies probiotic, has been reported to attenuate body weight gain, proinflammatory cytokines, and insulin resistance in mice fed a high-fat diet (12).…”
Section: Introductionmentioning
confidence: 99%
“…27 Although the majority of studies use single strains, supplementation with probiotic mixtures might have a greater efficacy. 28 Germ-free animals represent a unique tool to study the interactions of hosts with specific probiotic strains or with defined probiotic mixtures and to investigate their impacts on the development of the immune system. 6,29 Using a mouse model of allergic sensitization to the major birch pollen allergen Bet v 1, we have previously shown that neonatal colonization of GF mice with Bifidobacterium longum is able to prevent allergic sensitization, 20 but the underlying mechanism of the host-bacteria interaction in gnotobiotic models is still far from being elucidated.…”
Section: Introductionmentioning
confidence: 99%